ANALISIS DETERMINAN PERTUMBUHAN EKONOMI DI INDONESIA - Iffa Khaerunnisa Azzahro; Jalu Aji Prakoso (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
This study aims to determine the effect of the independent variables, namely poverty, LFPR, and unemployment, on economic growth in Indonesia. The data used is secondary data in the form of time-series data from 1991 to 2020. This study uses the Error Correction Model (ECM) approach. The analysis results show that the LFPR and unemployment variables in the short and long term have no significant effect on economic growth. At the same time, the variable of poverty in the short term and long term has a significant influence on economic growth